Structure-directing effects of ionic liquids in the ionothermal synthesis of metal–organic frameworks - Vaid, Thomas P. (IUCrJ, 2017)
Traditional synthesis of metal–organic frameworks (MOFs) involves the reaction of a metal-containing precursor with an organic linker in an organic solvent at an elevated temperature, in what is termed a ‘solvothermal’ reaction. More recently, many examples have been reported of MOF synthesis in ionic liquids (ILs), rather than an organic solvent, in ‘ionothermal’ reactions. The high concentration of both cations and anions in an ionic liquid allows for the formation of new MOF structures in which the IL cation or anion or both are incorporated into the MOF. Most commonly, the IL cation is included in the open cavities of the MOF, countering the anionic charge of the MOF framework itself and acting as a template around which the MOF structure forms. Ionic liquids can also serve other structure-directing roles, for example, when an IL containing a single enantiomer of a chiral anion leads to a homochiral MOF, even though the IL anion is not itself incorporated into the MOF. A comprehensive review of ionothermal syntheses of MOFs, and the structure-directing effects of the ILs, is given.